Let $X$ be a Hilbert space and $A\in\mathcal{L}(X)$ and $\displaystyle T(t)=e^{At}=\sum_{n=0}^{\infty}\frac{(At)^{n}}{n!}$.

I want to show that $T(t+\tau)=T(t)T(\tau)$.

So we have that $\displaystyle T(t+\tau)=e^{A(t+\tau)}=\sum_{n=0}^{\infty}\frac{(A(t+\tau))^{n}}{n!}=\sum_{n=0}^{\infty}\frac{(At)^{n}+(A\tau)^{n}}{n!}$.

I don't really know where to go from here.

  • $\begingroup$ You need to fix the last equation first. $(A(t+\tau))^n=A^n(t+\tau)^n=A^n\sum_{k=0}^{n}\binom{n}{k}t^k\tau^{n-k}$. Then multiply the series for $e^{At}$ and $e^{A\tau}$ and compare. $\endgroup$
    – Nathanson
    Mar 27, 2015 at 14:33

1 Answer 1


You made a mistake in the last step : $(A(t + \tau))^n \neq (At)^n + (A\tau)^n$. Note

$$[A(t + \tau)]^n = (At + A\tau)^n = \sum_{k = 0}^n\binom{n}{k} (At)^k(A\tau)^{n-k}$$

for all $n\in \Bbb N\cup \{0\}$, thus

\begin{align}\sum_{n = 0}^\infty \frac{[A(t + \tau)]^n}{n!} &= \sum_{n = 0}^\infty \sum_{k = 0}^n \frac{1}{n!}\binom{n}{k}(At)^k(A\tau)^{n-k}\\ & = \sum_{k = 0}^\infty \sum_{n = k}^\infty \frac{(At)^k(A\tau)^{n-k}}{k!(n-k)!}\\ & = \sum_{k = 0}^\infty \sum_{n = 0}^\infty \frac{(At)^k(A\tau)^n}{k!n!}\\ & = \sum_{k = 0}^\infty \frac{(At)^k}{k!}\sum_{n = 0}^\infty \frac{(A\tau)^n}{n!}\\ & = T(t)T(\tau). \end{align}

N.B. You could also write $[A(t + \tau)]^n = A^n\sum_{k = 0}^n \binom{n}{k}t^k\tau^{n-k}I$, and solve the problem from there. The method I used can be used to show more generally that $e^{X + Y} = e^{X}e^Y$ whenever $X$ and $Y$ commute.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.